2022
DOI: 10.3390/pharmaceutics14050919
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating Pathway and Anesthetic Mechanism of Action of Clove Oil Nanoformulations in Fish

Abstract: Clove oil (CO), an essential oil of Syzygium aromaticum, has been reported as an anesthetic for many fish species. However, its insoluble properties require a suitable delivery system for its application. In the present study, nanoformulations of CO as a nanoemulsion (CO-NE), a self-microemulsifying drug-delivery system (CO-SMEDDS), and a self-nanoemulsifying drug-delivery system (CO-SNEDDS) were prepared for delivering CO. Zebrafish were used as a fish model to investigate oil pathways. The result shows fluor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 45 publications
(48 reference statements)
1
6
0
Order By: Relevance
“…A second mechanisms that may contribute to the effect of eugenol to induce a drop in EOD frequency is its ability to potentiate GABA A -receptor response. Such an effect has been observed in test systems based on GABA A receptors expressed in Xenopus oocytes (Aoshima and Hamamoto 1999 ; Sahin et al 2017 ) 1 and is consistent with the results obtained in a [ 3 H] muscimol-binding assay using rat cortical homogenate (Kheawfu et al 2022 ). Since GABA application to the SPPn lowers the frequency of the EOD, and thus the output frequency of the Pn (Metzner 1999 ), a potentiation of the response of GABA receptors received by input from the nE↓ would be expected to result in a decrease of the oscillation frequency of the Pn.…”
Section: Discussionsupporting
confidence: 85%
“…A second mechanisms that may contribute to the effect of eugenol to induce a drop in EOD frequency is its ability to potentiate GABA A -receptor response. Such an effect has been observed in test systems based on GABA A receptors expressed in Xenopus oocytes (Aoshima and Hamamoto 1999 ; Sahin et al 2017 ) 1 and is consistent with the results obtained in a [ 3 H] muscimol-binding assay using rat cortical homogenate (Kheawfu et al 2022 ). Since GABA application to the SPPn lowers the frequency of the EOD, and thus the output frequency of the Pn (Metzner 1999 ), a potentiation of the response of GABA receptors received by input from the nE↓ would be expected to result in a decrease of the oscillation frequency of the Pn.…”
Section: Discussionsupporting
confidence: 85%
“…In general, clove oil was an efficient anesthetic at low concentrations (Fernandez et al, 2017). According to Kheawfu et al, (2022), the anesthetic mechanism of action of clove oil is based on the modulation of [ 3 H] muscimol binding to GABAA receptors located in the brain. Clove oil exerted a conspicuous depression of muscle contraction power (Fujimoto et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, anesthesia may inhibit neural and motor activity in the animals by blocking voltage-dependent K+ and Na+ channels [ 50 ]. Furthermore, the previous studies reported that eugenol and isoeugenol can activate the GABA A receptor in the central nervous system [ 30 , 51 , 52 ]. Therefore, we infer that the small particle and lipophilic nature of CO-NLCs have a tranquilizing effect on the brain and thereby potentiate the GABA A receptors’ response.…”
Section: Discussionmentioning
confidence: 99%
“…In this experiment, we investigated the biodistribution of fluorescently labeled clove oil in shrimp bodies visualized by bioluminescence imaging [ 30 ]. Shrimps were divided into three groups: control (untreated), STD-CO, and CO-NLCs.…”
Section: Methodsmentioning
confidence: 99%